Integrating Kahoot! in ESP courses: Vietnamese technical students’ perspectives - Thi Duyen Phuong; Thi Thanh Huyen Phuong (Institute of Advanced Engineering and Science, 2026)
This study investigates the integration of Kahoot!, an online gamified platform, in an English for specific purposes (ESP) course at a Vietnamese state-run university. The study examines Kahoot!-use frequency and students perception of its effectiveness in supporting classroom and autonomous learning. Using an explanatory mixed-methods design, the study draws on survey data from 87 technical students and focus groups with 10 volunteers. Findings indicate that while Kahoot! was frequently used in class, its use outside classrooms was limited by insufficient teacher support. Although gamified tasks were perceived as engaging and useful, misalignments between instructional practices and learners’ expectations, including over-emphasis on vocabulary and grammar, inappropriate pacing, insufficient feedback, and overly challenging tasks, reduced its effectiveness and motivational impact. The study highlights the need to align gamified pedagogy with ESP learners’ needs, use platform analytics for pedagogical adaptation, and use Kahoot! beyond classrooms to enhance learners’ engagement and autonomy.